Efficient Sensitivity Reducing and Hygroscopicity Preventing of Ultra‐Fine Ammonium Perchlorate for High Burning‐Rate Propellants. Issue 7 (20th February 2017) - Yang, Zhijian; Gong, Feiyan; Ding, Ling; Li, Yubin; Yang, Guangcheng; Nie, Fude
Abstract: In this research, several inert materials, including some functional carbon materials, paraffin wax and the well‐known insensitive energetic material 1, 3, 5‐triamino‐2, 4, 6‐trinitrobenzene (TATB) were selected to reduce the undesirable high sensitivity and hygroscopicity of ultra‐fine ammonium perchlorate (UF‐AP) via polymer modified coating. Structure, sensitivity, thermal and hygroscopicity performances of the UF‐AP based composites were systematically studied by scanning electron microscopy, sensitivity tests, thermal experiments, contact angle, and hygroscopicity analysis. The results showed that both the impact and friction sensitivity of UF‐AP can be remarkably reduced, respectively, with only a small amount of 2 % (in mass) desensitization agents. Meanwhile, improved thermal decomposition was gained, and the hygroscopicity can also be reduced to a large extent. Propellants containing 10 % coated UF‐AP in mass were processed and tested, the burning rate reached 45.7 mm s −1, 50 % higher compared with that of normal AP, with remarkably reduced impact sensitivity from 11.5 J to 29.6 J and friction sensitivity from 76 % to 28 %. Abstract :